2016
DOI: 10.1186/s12936-016-1627-5
|View full text |Cite
|
Sign up to set email alerts
|

Provider and user acceptability of intermittent screening and treatment for the control of malaria in pregnancy in Malawi

Abstract: BackgroundMalaria in pregnancy is a major cause of adverse maternal and fetal outcomes. Intermittent preventive treatment with sulfadoxine–pyrimethamine (IPTp-SP) is one of the control strategies promoted by WHO. In response to mounting resistance to SP, intermittent screening and treatment (ISTp) has been proposed as an alternative. The objective of this study was to explore the acceptability of ISTp for health workers and pregnant women.MethodsSemi-structured interviews of ten health workers and five focus g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Notwithstanding the unavailability of RDTs, all health provider cadres expressed a lack of confidence in RDT test results such that midwives would refer symptomatic patients with a negative RDT result to a health centre for confirmation by microscopy. Poor acceptability and adherence to RDT test results has also been reported in similar studies in pregnant women in Kenya and Malawi [ 20 , 21 ]. Ultra-sensitive diagnostic tests that have recently become available on the market (e.g.…”
Section: Discussionmentioning
confidence: 53%
“…Notwithstanding the unavailability of RDTs, all health provider cadres expressed a lack of confidence in RDT test results such that midwives would refer symptomatic patients with a negative RDT result to a health centre for confirmation by microscopy. Poor acceptability and adherence to RDT test results has also been reported in similar studies in pregnant women in Kenya and Malawi [ 20 , 21 ]. Ultra-sensitive diagnostic tests that have recently become available on the market (e.g.…”
Section: Discussionmentioning
confidence: 53%
“…Primarily, giving anti-malarials presumptively was against current national policy, but there were also concerns about causing potential harm to mother and baby and of driving drug resistance. This view is a sharp contrast to studies from Africa where IPTp is widely used to prevent malaria in pregnancy, and health provider acceptance of prevention over treatment is strong [ 13 , 15 ]. In contrast, in Sumba and Mimika the concept of giving drugs before receiving a positive test was seen as a form of malpractice with some providers emphatically stating they would never do such a thing.…”
Section: Discussionmentioning
confidence: 82%
“…Weekly screening for malaria by microscopy and treatment of test positive women with effective anti-malarials substantially reduced maternal mortality from P. falciparum malaria in refugee camps on the Thai-Myanmar border [ 8 ], however such intensive screening programmes are unlikely to be feasible in routine health system settings. Recent trials in sub-Saharan Africa [ 9 12 ] found intermittent screening and treatment in pregnancy (ISTp) with RDTs at every scheduled ANC visit (average of 3–6 visits) and treatment of positive cases with artemisinin-based combination therapy (ACT) was acceptable and potentially feasible [ 13 16 ]. However, recent results from the clinical trials indicate that, with the current generation of malaria RDTs, ISTp was not a suitable alternative strategy to intermittent preventive treatment with sulfadoxine–pyrimethamine (IPTp-SP), even in areas with high prevalence of SP resistance in East and Southern Africa [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Necessity of machines maintenance, reagents supply and quality control assurance need also to be considered in a medium and long term approach for decentralized laboratories. Good acceptability of capillary blood sampling is another advantage of DBS when compared with venepuncture (Pell et al, 2014;Almond et al, 2016). In this context, sampling on DBS considers decentralized sampling as possible, whilst carrying out the test in a well-equipped centralized clinical laboratory, without waiting for the uncertain availability of new technologies and without necessity of maintaining a cold chain for transportation ( Figure 1A).…”
Section: Indications Of Dbs In Infectious Diseasesmentioning
confidence: 99%